The Lived Experiences of International Students Who's Family Remains At Home - Harvey, Theresa; Robinson, Carolyn; Welch, Anthony (Journal of International Students, 2018)
The significant increase of international students, who leave their family at home, to study abroad, especially in the discipline of nursing, has implications for educational practice. This study’s aim was to explore adult international students’ experiences of leaving spouse and children – for further education overseas. A descriptive phenomenological approach to inquiry using Colaizzi’s (1978) analysis framework revealed four themes: living with emotional turmoil, living in a world of negativity, living with an expectation to cope and driven by personal ambition. The findings identified a hidden world of emotional trauma, psychological stress, and negativity, specifically related to relinquishing their role in the family. The authors conclude that an ‘open door policy’ that provides individual counselling and timely support for academic and social purposes is necessary.